The Role of Multiparametric Magnetic Resonance in Volumetric Modulated Arc Radiation Therapy Planning for Prostate Cancer Recurrence After Radical Prostatectomy: A Pilot Study - Sardaro, Angela; Turi, Barbara; Bardoscia, Lilia; Ferrari, Cristina; Rubini, Giuseppe; Calabrese, Angela; Ammirati, Federica; Grillo, Antonietta; Leo, Annamaria; Lorusso, Filomenamila; Santorsola, Antonio; Stabile Ianora, Antonio Amato; et al. (Frontiers in Oncology, 2021)
Background and Purpose: Volumetric modulated arc radiotherapy (RT) has become pivotal in the treatment of prostate cancer recurrence (RPC), to optimize dose distribution and minimize toxicity thanks to the high-precision delineation of prostate bed contours and organs at risk (OARs) under multiparametric magnetic resonance (mpMRI) guidance. We aimed to assess the role of pre-treatment mpMRI in ensuring target volume coverage and normal tissue sparing. Material and Methods: Patients with post-prostatectomy RPC eligible for salvage RT were prospectively recruited to this pilot study. Image registration between planning CT scan and T2w pre-treatment mpMRI was performed. Two sets of volumes were outlined, and DWI images/ADC maps were used to facilitate precise gross tumor volume (GTV) delineation on morphological MRI scans. Two rival plans (mpMRI-based or not) were drawn up. Results: Ten patients with evidence of RPC after prostatectomy were eligible. Preliminary data showed lower mpMRI-based clinical target volumes than CT-based RT planning (p=0.0003): median volume difference 17.5 cm3. There were no differences in the boost volume coverage nor the dose delivered to the femoral heads and penile bulb, but median rectal and bladder V70Gy was 4% less (p=0.005 and p=0.210, respectively) for mpMRI-based segmentation. Conclusions: mpMRI provides high-precision target delineation and improves the accuracy of RT planning for post-prostatectomy RPC, ensures better volume coverage with better OARs sparing and allows non homogeneous dose distribution, with an aggressive dose escalation to the GTV. Randomized phase III trials and wider datasets are needed to fully assess the role of mpMRI in optimizing therapeutic strategies.